Analisa Faktor-Faktor Dining Experience dalam Menciptakan Minat Beli Ulang di Café “Kantin” Kota Palembang - Andhika Chandra Lesmana (Manajemen dan Pariwisata, 2023)
The phenomenon of establishing coffee shops in Indonesia has become a trend in recent years. This can be seen from the significant increase in the number of coffee shops and domestic coffee consumption in recent years. Palembang is one of the cities in Indonesia, especially southern Sumatra, which cannot be separated from the growth of coffee shops or often known as cafes. Of course, the role of experience felt by consumers is a separate assessment for a cafe which will later become a differentiator in every place, especially cafes which are expected to provide a positive experience for people to come and buy the product again. This research aims to analyze more deeply the Dining Experience Factors in Creating Repurchase Interest in the "Kantin" Cafe, Palembang City. The method used in this research is a quantitative method with a descriptive approach, with data collection techniques in the form of observation, questionnaires, interviews, documentation studies and literature studies. The research results stated that in the Dining Experience variable the majority of respondents "agree" with a percentage of 47%. And of the 3 dimensions of Dining Experience that received a positive response was the Food Quality dimension, this can be seen with the majority of respondents answering "agree" with 70% in the aspect "Quantity or portion of food as expected". The magnitude of the relationship that occurs between Dining Experience and Repurchase Intention has a strong and significant relationship, where the profitability significance value is 0.716 which is greater than 0.50.